Prominent subcutaneous oedema as a masquerading symptom of an underlying inflammatory myopathy. Issue 2 (February 2017) - Anantharajah, Anthea; Vucic, Steve; Tarafdar, Surjit; Vongsuvanh, Roslyn; Wilcken, Nicholas; Swaminathan, Sanjay
Abstract : The inflammatory myopathies are a group of immune‐mediated inflammatory muscle disorders that typically present with marked proximal muscle weakness. We report four cases of inflammatory myopathies with marked subcutaneous oedema as their main complaint. Three of the four patients had normal or low levels of creatine kinase, an enzyme often markedly elevated in these disorders. Magnetic resonance imaging of the muscles, followed by a muscle biopsy were used to make a definitive diagnosis.